Latex allergy: epidemiological study of 1351 hospital workers. Issue 5 (May 1997) - Liss, G M; Sussman, G L; Deal, K; Brown, S; Cividino, M; Siu, S; Beezhold, D H; Smith, G; Swanson, M C; Yunginger, J; Douglas, A; Holness, D L; et al.
Abstract : OBJECTIVE: To determine the prevalence of latex sensitisation among a large group of healthcare workers, study the occupational and non-occupational factors associated with latex allergy, and characterise latex exposure in air and by gloves. METHODS: All 2062 employees of a general hospital in Hamilton, Ontario, Canada who regularly used latex gloves were invited to participate in a cross sectional survey, representing the baseline phase of a prospective cohort morbidity study. Attempts were made to recruit employees who were diagnosed with latex allergy before the survey. Glove extracts were assayed for antigenic protein, and area and personal air samples were obtained on two occasions (summer and winter) to estimate exposure to airborne latex protein. A questionnaire on medical and occupational information was administered by an interviewer. Skin prick tests were performed with latex reagents, three common inhalants, and six foods. RESULTS: The mean (SD) latex protein concentrations were 324 (227) micrograms/g in powdered surgical gloves and 198 (104) micrograms/g in powdered examination gloves. Personal latex aeroallergen concentrations ranged from 5 to 616 ng/m3. There was a total of 1351 (66%) participants. The prevalence of positive latex skin tests was 12.1% (95% confidence interval (95% CI) 10.3% to 13.9%). This prevalence did not vary by sex, age, hospital, or smoking status but subjects who were latex positive were significantly more likely to be atopic (P < 0.01). Participants who were latex positive were also significantly more likely to have positive skin tests to one or more foods (Mantel-Haenszel odds ratio (OR) adjusted for atopy 12.1, 95% CI 7.6 to 19.6, P < 10(-9)). Work related symptoms were more often reported among latex positive people, and included hives (OR 6.3, 95% CI 3.2 to 12.5), eye symptoms (OR 1.9, 95% CI 1.2 to 2.8), and wheezy or whistling chest (OR 4.7, 95% CI 2.8 to 7.9). The prevalence of latex sensitivity was highest among laboratory workers (16.9%), and nurses and physicians (13.3%). When the glove consumption per healthcare worker for each department was grouped into tertiles, the prevalence of latex skin test positivity was greater in the higher tertiles of glove use for sterile (surgical) gloves (P < 0.005) but not for examination gloves. CONCLUSIONS: In this large, cross sectional study of healthcare workers, the prevalence of latex sensitisation was 12.1% (9.5% among all those eligible), and there were significant associations with atopy, positive skin tests to certain foods, work related symptoms, and departmental use of gloves per healthcare worker. This cohort is being followed up prospectively and will be retested to determine the incidence of development of latex sensitivity.